Tribocorrosion behaviour of Ti6Al4V in artificial seawater at low contact pressures. (March 2018) - Pejaković, Vladimir; Totolin, Vladimir; Rodríguez Ripoll, Manel
Abstract: The tribo-electrochemical performance of Ti6Al4V in artificial seawater is investigated under reciprocating sliding conditions at three contact loads (10 mN, 100 mN, and 1 N) and three electrochemical conditions (−0.5 V, OCP and +0.5 V). The results reveal that the achieved contact pressures are not able to fully depassivate the surface. For the lowest load, no rupture on the passive film could be detected while with an increase in the load, depassivation-repassivation takes place during sliding contact. For 100 mN, an unusual higher coefficient of friction was measured for all electrochemical testing conditions. This behaviour is observed to correlate with a higher synergy between corrosion and wear and seems to be linked with the initial surface roughness of the titanium alloy. Highlights: No depassivation measurable for loads of 10 mN. The coefficient of friction is abnormally high at 100 mN independently of the electrochemical conditions. Abnormally high COF at 100 mN is due to roughness and resulting generation of third body particles. The relation between contact load and roughness is able to justify the observed friction behaviour.